Unmasking Ethical Bias in Tax Behavior: A Study of Machiavellian Traits, Emotional Intelligence, and Love of Money - Dien Noviany Rahmatika (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
This study employs a behavioral accounting perspective to analyze the influence of Machiavellian Traits and emotional intelligence on ethical attitudes toward tax evasion, with love of money as a mediating variable. Using purposive sampling of 100 accounting students from three universities in Central Java who had completed auditing and taxation courses, data were analyzed using PLS-SEM. Results indicate that Machiavellian Traits, emotional intelligence, and money attachment significantly influence ethical judgments regarding tax evasion. Love of money was found to mediate the relationship between Machiavellian Traits and emotional intelligence with ethical assessments. This triadic model demonstrates that ethical tax decisions are influenced by personality traits, value systems, and cognitive factors. The findings provide implications for ethics education, behavioral tax policy, and designing compliance frameworks that consider individual psychological profiles, challenging conventional assumptions and expanding existing knowledge boundaries.